Pengembangan Perangkat Pembelajaran Berbasis Potensi Daerah Melalui Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar Kognitif IPA Biologi Siswa SMP Negeri 2 Tenggarong Seberang - Turini, Turini; Rambitan, Vandalita M. M.; Maasawet, Elsje Theodora (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The background of this research is that some teachers only know the term regional potential but cannot explain the exact meaning of dar regional potential-based learning. So that the teacher has not been able to pour it in a learning process that is supported by a learning model cooperative to improve learning outcomes. Hence this study aims to: 1) To develop regional potential-based learning tools through guided inquiry, 2) To find out the feasibility of developing war equipment regional potential-based learning through guided inquiry to improve Cognitive learning outcomes of Biology Science students at SMP Negeri 2 Tenggarong Seberang. 3) For know the effectiveness of regional potential-based learning tools through guided inquiry to improve the cognitive learning outcomes of Science Biology Junior High School Students Negeri 2 Tenggarong Seberang. This development research refers todevelopment steps with the Thiagarajan model. By design The development is grouped into 3 development procedures includes: (a) the define stage (definition), (b) the design stage (design), and (c) the stage development (development). Product testing consists of validation tests that are carried out by learning device experts and linguists as well as device feasibility testing learning. Collecting data using observation guidelines and questionnaires for device experts, languages and practitioners an average of 61,07 with qualifications less worthy to be 89,76 with very decent qualifications, which means this device is very feasible to use. This research resulted in (1) regional potential-based learning tools through guided inquiry, (2) the resulting devices increased the results. students' cognitive learning with the difference in the percentage gain score test of the control class and experimental class with very good category 11%, good 14% and enough well -25%. The average value of student learning outcomes for the control class was 44,78 to be 78,14, while the average value for the experimental class was 54,5 to 82,32. As has been proven that the value of class learning outcomes experiment is higher than the control class can be seen in the independent t-testl sig.2-tailed with a number of 0,030 < 0,05. Comparison of t count to the t table of 2,234>1,70329. This proves a learning tool based on regional potential through guided inquiry to improve learning outcomes Cognitive Science Biology effectively used by students of SMP Negeri 2 Temggarong Seberang